Bangladesh-India relations : perspectives from civil society dialogues - Sobhan, Rehman; Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press, 2002)
Report of the Indo-Bangladesh dialogues held during February 1, 1995 to January 16, 2001.
"Centre for Policy Dialogue."
Keywords: Bangladesh -- Relations -- India; India -- Relations -- Bangladesh